2010
DOI: 10.4269/ajtmh.2010.08-0668
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns in kdr Frequency in Permethrin and DDT Resistant Anopheles gambiae s.s. from Uganda

Abstract: The planned upscaling of vector control strategies requires insight into the epidemiological consequences of vector resistance. Therefore, the pyrethroid and DDT resistance status of Anopheles gambiae s.l. was assessed in Uganda from 2004 to 2006, and spatial and seasonal variations in knockdown resistance (kdr) frequencies were analyzed in terms of epidemiological significance. Anopheles gambiae s.l. was DDT and pyrethroid resistant in central and eastern Uganda. The L1014S kdr allele frequencies varied from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 30 publications
5
70
0
Order By: Relevance
“…It has been reported before that kdr allele frequencies can vary seasonally, and in our data, samples were pooled for an entire year. 19,62,63 We also have shown that selection has acted strongly on this locus after the application of pyrethroid insecticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported before that kdr allele frequencies can vary seasonally, and in our data, samples were pooled for an entire year. 19,62,63 We also have shown that selection has acted strongly on this locus after the application of pyrethroid insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae sensu stricto in three out five sites during 2001-2002 and 2004-2006. 19 In Ethiopia, L1014F allele frequencies in excess of 98% were found in An. arabiensis exposed to DDT, which was used for IRS and ITN control measures.…”
Section: L1014s Frequencies Doubled From Approximately 3-4% Inmentioning
confidence: 99%
“…gambiae and An. arabiensis (Ramphul et al 2009; Verhaeghen et al 2010; Mawejje et al 2013) and An. funestus (Morgan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These small-scale IRS programs were performed sporadically during the following decades, but their impacts on plague in Uganda were never evaluated (UMCP 2005). Currently, IRS is part of the Uganda Malaria Control Strategic Plan that is supported in part by the PresidentÕs Malaria Initiative (PMI) (UMCP 2005, Verhaeghen et al 2010) and covers only a portion of the country (six districts in north central Uganda), but not including the plagueendemic region of northwestern Uganda. Since 2007, these districts have consistently had Ͼ90% of their households sprayed with IRS by the PMI program (USAID 2010).…”
mentioning
confidence: 99%